Tilting Behavior of Lamellar Ice Tip during Unidirectional Freezing of Aqueous Solutions - Zhang, Tongxin (Langmuir : the ACS journal of surfaces and colloids, 2021)
Freezing of ice has been largely reported from many aspects, especially its complex pattern formation. Ice grown from liquid phase is usually characteristic of lamellar morphology that plays a significant role in various domains. However, tilted growth of ice via transition from coplanar to noncoplanar in directional solidification has been paid little attention in previous studies and there was a misleading explanation of the formation of tilted lamellar ice. Here, we in situ investigated the variations of tilting behavior of lamellar ice tips under different conditions within a single ice crystal of manipulated orientation via unidirectional freezing of aqueous solutions. It is found that tilted growth of ice tips is sensitive to pulling velocity and solute type. These experimental results reveal intrinsic tilted growth behavior of lamellar ice, which is suggested to enrich our understanding of pattern formation of ice in relevant physical processes